Anti-Mitochondrial Antibody Titers Decrease Over Time in Primary Biliary Cholangitis Patients With Ursodeoxycholic Acid Therapeutic Response: A Cohort Study Followed Up to 28 Years - Chang, Ming-Ling; Chen, Wei-Ting; Chan, Tien-Ming; Lin, Cheng-Yu; Chang, Ming-Yu; Chen, Shiang-Chi; Chien, Rong-Nan (Frontiers in Immunology, 2022)
Background How anti-mitochondrial antibody (AMA) and liver biochemistry levels change in primary biliary cholangitis (PBC) patients treated with ursodeoxycholic acid (UDCA) remains unclear. Methods A 28-year cohort of 157 PBC patients was conducted. Patients with alkaline phosphatase (Alk-p) levels >1.67 × upper limit of normal after 1 year of UDCA treatment were considered nonresponders. Results At baseline, of 157 (mean age: 54.41 years), 136 (86.6%) were female, 51 (32.5%) had cirrhosis, and 128 (81.5%) had detectable AMAs (immunoglobulin G). UDCA nonresponders (n=61) were younger and had higher Alk-p and total bilirubin levels and cirrhosis rates than UDCA responders (n=84). Alk-p levels and cirrhosis were negatively associated with UDCA response. Regardless of cirrhosis and UDCA response, most PBC patients had decreased Alk-p and γ-glutamyltransferase levels at last follow-up (up to 28.73 years) compared with baseline levels. Patients with baseline cirrhosis (2.78 ± 2.56 vs. 6.84 ± 9.00 mg/dL, p=0.024) and UDCA nonresponders (2.54 ± 2.19 vs. 4.51 ± 6.99 mg/dL, p=0.006) had increased total bilirubin levels while patients without cirrhosis (AST: 91.5 ± 84.5 vs. 58.9 ± 43.7 U/L, p<0.001; ALT: 107.3 ± 122.5 vs. 50.7 ± 36.8 U/L, p<0.001) and UDCA responders (AST: 83.8 ± 101.3 vs. 45.58 ± 38.42 U/L, p=0.014; ALT: 95.10 ± 144.6 vs. 39.12 ± 30.65 U/L, p=0.009) had decreased aminotransferase levels. Only UDCA responders had decreased AMA titers from 1 year after UDCA treatment (p=0.028) until the last follow-up (p<0.001). Conclusions UDCA responders exhibited decreased AMA titers 1 year after treatment. Regardless of UDCA response, PBC patients showed improved cholestatic features, but only UDCA responders and patients without baseline cirrhosis exhibited attenuated hepatobiliary damage following UDCA treatment.